Value addition in district level dynamical forecast during intense rainfall spells over the west coast of India - LAL, B.; SINGH , O. P.; PRASAD, ONKARI (MAUSAM, 2006)
lkj & ekulwu _rq ds nkSjku Hkkjr ds if’peh rV ij Hkkjh o"kkZ dh ?kVukvksa dk vjc lkxj ds Åij iouksa dh vf/kdre xfr ds ØksM ¼dksj½ ds lkFk ?kfu"B laca/k gSA bl 'kks/k&i= esa bZ- lh- ,e- MCY;w- ,Q- ¼;wjksih; e/;e vof/k iwokZuqeku dsUnz½ }kjk 850 gSDVkikLdy ij iwokZuqekfur 72 ?kaVs ds izokg izfr:i dk mi;ksx fd;k x;k gS ftlls if’peh rV ij Hkkjh o"kkZ dk iwokZuqeku djus ds fy, ftyk Lrjh; xfrdh; iwokZuqeku iz.kkyh dh {kerk c<+kus gsrq ek=kRed i)fr dk fodkl fd;k tk ldsA ;g ns[kk x;k gS fd if’peh rV ij o"kkZ dh ek=k dk if’peh rV ij vjc lkxj esa iou dh vf/kdre xfr ds 72 ?kaVs ds bZ- lh- ,e- MCY;w- ,Q- }kjk fd, x, iwokZuqeku ds lkFk egRoiq.kZ lglaca/k gSA if’peh rV ij Hkkjh o"kkZ ds {ks= ds v{kka’kh; foLrkj dk if’peh rV ij iou dh vf/kdre xfr ds ØksM ¼dksj½ ds lkFk egRoiw.kZ lglaca/k gSA bl 'kks/k&i= esa ;g crk;k x;k gS fd xzh"edkyhu ekulwu _rq ds nkSjku Hkkjr ds if’peh rV ij Hkkjh o"kkZ ds 72 ?kaVs dk iwokZuqeku djus ds fy, iouksa dh vf/kdre xfr ds 72 ?kaVs ds iwokZuqekfur ØksM ¼dksj½ vkSj foLrkj dh rhozrk vkSj fLFkfr dh {kerk c<+kus ds fy, laHkkfor iwoZlwpdksa ds :i esa mi;ksx fd;k tk ldrk gSA Occurrences of intense rainfall events over west coast of India during monsoon are intimately linked to the core of maximum winds over the Arabian Sea. ECMWF (Europian Centre for Medium Range Weather Forecasting ) predicted 72 hr flow pattern at 850 hPa has been used to develop a quantitative method for value addition in the district level dynamical forecast system for intense rainfall over the west coast. It has been found that the amount of rainfall over the west coast is significantly correlated to 72 hr ECMWF forecast of maximum wind speed over the Arabian Sea along the west coast. The latitudinal width of the heavy rainfall belt over the west coast has got significant correlation with the location of maximum wind core along the west coast. It has been shown that the strength and location of the 72 hr predicted core and fetch of maximum winds could be used as potential predictors in the value addition for 72 hr heavy rainfall forecast along the west coast of India during summer monsoon.